2017
DOI: 10.4172/2155-6148.1000769
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex Efficacy for Rapid Reversal of Rocuronium Induced Neuromuscular Blockade in Pediatric Rigid Bronchoscopy Regardless the Depth of Anesthesia

Abstract: Background: Bronchoscopy may be either rigid or flexible. Rigid bronchoscopy is usually done for diagnosis and treatment of intra and/or extra luminal obstruction in the airway for adults and children, anaesthesia for bronchoscopy poses unique challenges for the anaesthesiologist. This procedure needs specific technical precision because both the anaesthesiologist and operator share the same working space, that is, the airway. Pediatric rigid bronchoscopy needs a deep level of general anesthesia with a good (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Won et al 21 reported that although there was no significant difference in the incidence of adverse events in pediatric patients, sugammadex provided a faster reversal of rocuronium-induced neuromuscular blockade and a shorter extubation time compared to atropineneostigmine. Mogahed, et al 22 reported that sugammadex reversed the effect of rocuronium significantly faster than neostigmine. In our study, recovery time was 10 minutes in patients using sugammadex and 16.4 minutes in patients using Neostigmine.…”
Section: Discussionmentioning
confidence: 99%
“…Won et al 21 reported that although there was no significant difference in the incidence of adverse events in pediatric patients, sugammadex provided a faster reversal of rocuronium-induced neuromuscular blockade and a shorter extubation time compared to atropineneostigmine. Mogahed, et al 22 reported that sugammadex reversed the effect of rocuronium significantly faster than neostigmine. In our study, recovery time was 10 minutes in patients using sugammadex and 16.4 minutes in patients using Neostigmine.…”
Section: Discussionmentioning
confidence: 99%